2023
DOI: 10.1038/s41398-023-02416-3
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the microbiome to understand clinical heterogeneity in depression: findings from the T-RAD study

Abstract: Alterations in the gut microbiome have been linked to a variety of mental illnesses including anxiety and depression. This study utilized advanced bioinformatics tools that integrated both the compositional and community nature of gut microbiota to investigate how gut microbiota influence clinical symptoms in a sample of participants with depression. Gut microbiota of 179 participants with major depressive disorder (MDD) in the Texas Resilience Against Depression (T-RAD) study were analyzed by 16S rRNA gene se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 66 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…These results support the findings of several other studies that there is a unique microbiota signature associated with ANXD and MDD. For example, the Texas Resilience Against Depression identified a network of microbes that commonly co-occur in participants with MDD (54). These signatures are not exclusive to the stool microbiota: another study identified negative associations between the Bacteroidaceae family and Bacteroides genus with depression symptoms, along with positive associations between the Desulfovibrionaceae family and Clostridiales Family XIII with anxiety symptoms in the serum microbiota, while another found links between members of the oral microbiota and MDD (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…These results support the findings of several other studies that there is a unique microbiota signature associated with ANXD and MDD. For example, the Texas Resilience Against Depression identified a network of microbes that commonly co-occur in participants with MDD (54). These signatures are not exclusive to the stool microbiota: another study identified negative associations between the Bacteroidaceae family and Bacteroides genus with depression symptoms, along with positive associations between the Desulfovibrionaceae family and Clostridiales Family XIII with anxiety symptoms in the serum microbiota, while another found links between members of the oral microbiota and MDD (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Ruminococcaceae UCG011 and genus Ruminococcaceae UCG010 , belonging to family Ruminococcaceae , have been reported as associated with some diseases such as leukemia ( Chen et al, 2023 ), type 2 diabetes ( Li and Li, 2023 ), and esophageal cancer ( Wang et al, 2024 ), but they have yet to be studies in the context of mental health disorders. However, multiple clinical studies have demonstrated that psychological distress and mental illness, such as depression and anxiety, are associated with alterations in the abundance of Ruminococcaceae family members ( Chen et al, 2021 ; Chin Fatt et al, 2023 ), and animal studies have suggested that regulating the abundance of Ruminococcaceae family members with various interventions can promote the production of SCFAs and other neurochemical-related metabolites. These metabolites, in turn, modulate neurotransmitter-associated metabolism, inflammation, and the microbiota-gut-brain axis, thereby alleviating depressive and anxiety-like behaviors in different mouse models of chronic stress ( Chen Y. et al, 2022 ; Zhou et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential protective mechanisms of Ruminococcaceae and Anaerotruncus against MS might be associated with their role in increasing the production of butyrate in the gut (Bianchimano et al., 2022 ; Chin Fatt et al., 2023 ; Lee et al., 2023 ). Butyrate, acting as an inducer of Tregs (Haghikia et al., 2015 ), has been shown to promote oligodendrocyte differentiation, inhibit demyelination, and stimulate remyelination, reducing the risk of MS relapses and the emergence/extension of magnetic resonance imaging lesions (Chen et al., 2019 ; Horton et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%